THE DISSEMINATION OF TECHNOLOGY-BASED LEARNING MEDIA FOR ELEMENTARY SCHOOL TEACHERS IN THE DISTRICT OF SIJUNJUNG - Irfandi, Irfandi; Faisal, Faisal; Hasibuan, Novita Indah; Panggabean, Deo Demonta (Universitas Negeri Medan, 2018)
AbstractThe purpose of this program is to improve the ability and skills of teachers on the use of learning media of science in the elementary school (known as Sekolah Dasar in Bahasa; henceforth abbreviated as SD) at the district of Sijunjung in the province of Sumatera Barat, Indonesia. We encouraged respective teachers on modifying, creating and using learning media relevant to Science learning in SD. Thus, teachers are not only able to utilize the existing science learning media, but also to develop new learning media related to the subject. The output of the program is the guidebook that teachers can further use as a technical guideline in applying science learning media at SD. In assuring the quality of the program, the evaluation was conducted through process and result assessments. The mean score of 3.54 and 3.73 rooted from process and result assessments respectively indicating the performance of teachers applying science learning media at a very good category. In conclusion, the dissemination program of technology aids learning media science in elementary school teachers in the District of Sijunjung at the Province of West Sumatra was successfully implemented.Keywords: Science, Learning Media, Elementary School, Sijunjung, Sumatera Barat